2006
DOI: 10.1097/01.aids.0000200541.40633.56
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted acute infection with a clustered genotype 4 hepatitis C virus in HIV-1-infected men and inefficacy of early antiviral therapy

Abstract: There is a risk of sexual transmission of HCV in HIV-infected men who have sex with men; the cluster of HCV genotype 4d suggested a common source of infection and a failure in prevention counselling. Early treatment with standard interferon-alfa failed to prevent chronic evolution of HCV infection in this particular group of HIV-infected patients who had acquired this peculiar cluster of genotype 4 strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 44 publications
6
90
0
3
Order By: Relevance
“…Molecular typing of HCV isolates confirmed the presence of MSM-specific transmission networks in London [25], Paris [26] and Amsterdam [27]. A collaborative phylogenetic study revealed that these locally reported outbreaks were in fact part of one larger interconnected European transmission network [22].…”
Section: As Well As In the Unitedmentioning
confidence: 76%
See 1 more Smart Citation
“…Molecular typing of HCV isolates confirmed the presence of MSM-specific transmission networks in London [25], Paris [26] and Amsterdam [27]. A collaborative phylogenetic study revealed that these locally reported outbreaks were in fact part of one larger interconnected European transmission network [22].…”
Section: As Well As In the Unitedmentioning
confidence: 76%
“…However, recent outbreaks of acute HCV among HIV-positive MSM who deny IDU suggest that the epidemiology of HCV transmission is changing in this population. In several European countries [25][26][27] …”
Section: Hepatitis Bmentioning
confidence: 99%
“…No patient achieved SVR. 132 Finally, 9 acute HCV infections were identified in HIV-infected patients in California. 31 Only 4 were treated with pegylated interferon and RBV; 3 achieved SVR.…”
Section: Treatment Of Acute Hcv Infectionmentioning
confidence: 99%
“…16 Several outbreaks of acute HCV have also been reported across Europe among HIVpositive men who have sex with men; these individuals are associated with high-risk sexual practices. [17][18][19] It is unclear whether HCV infections influence the progression of HIV, but current data clearly suggest that HIV infections influence the development of HCVrelated liver disease. Among patients with decompensated cirrhosis, HIV/HCV-coinfected patients experience more rapid fibrosis progression and have poorer survival rates in comparison with HCV-monoinfected patients; their median estimated survival time is only 13 months.…”
Section: Viral Etiologiesmentioning
confidence: 99%